The girl on the train - Hawkins, Paula (New York : Riverhead Books, a member of Penguin Group (USA), 2015)
"Rachel takes the same commuter train every morning ... past a stretch of cozy suburban homes, and stops at the signal that allows her to daily watch the same couple breakfasting on their deck. She's even started to feel like she knows them ... Their life-as she sees it-is perfect. Not unlike the life she recently lost. And then she sees something shocking. It's only a minute until the train moves on, but it's enough. Now everything's changed. Unable to keep it to herself, Rachel offers what she knows to the police, and becomes inextricably entwined in what happens next, as well as in the lives of everyone involved. Has she done more harm than good?"--Provided by publisher.
Booklist starred, November 2014
Pub Weekly, November 2014
Kirkus Starred, November 2014
Adult
Adult
Booklist starred
Keywords: Railroad travel -- Fiction; Commuters -- Fiction; Strangers -- Fiction; London (England) -- Fiction; Travel -- Fiction; Railroads -- Fiction; Commuters -- Fiction; Strangers -- Fiction; London (England) -- Fiction; Psychological fiction; Mystery fiction; Psychological fiction; Suspense fiction